Commentary from the Editorial Board to Vitiligo: interplay between oxidative stress and immune system (Laddha et al.). Issue 6 (7th May 2013) - Colucci, Roberta; Böhm, Markus; Moretti, Silvia
Abstract Vitiligo pathogenesis is very puzzling, and novel mechanisms possibly involved in the development of this disorder are frequently explored. Recently, some authors proposed an interplay between oxidative stress and immune system at the basis of melanocyte loss. According to the experimental evidence, they suggest that exposition to environmental agents might lead to an association between vitiligo and other autoimmune diseases. Accordingly, it is proposed that increased reactive oxygen species due to environmental agents could induce a modification of both melanocytic structures and other tissue proteins, or might disregulate the immune system, influencing the appearance of vitiligo and autoimmune comorbidities.